40.6k views
3 votes
Simplify the expression below and explain which rules of exponents you used to simplify the expression. \frac{(16 \sqrt[]{x})^2 }{y^{-1}}

Simplify the expression below and explain which rules of exponents you used to simplify-example-1
User Sixthsense
by
4.5k points

1 Answer

4 votes

Given the following expression:


\frac{(16 \sqrt[]{x})^2 }{y^(-1)}

You need to remember the Rules of Exponents shown below:

- Negative Exponent Rule:


b^(-n)=(1)/(b^n)

Where "b" is the base and "n" is the exponent.

- Fractional Exponent Rule:


b^{(m)/(n)}=\sqrt[n]{b^m}

- Power of a Product Rule:


(ab)^m=a^mb^m

In this case, knowing the rules shown above, you can simplify the expression as follows:

1. Apply the Power of a Product Rule in the numerator:


=\frac{(16)^2(\sqrt[]{x})^2}{y^(-1)}=\frac{256^{}(\sqrt[]{x})^2}{y^(-1)}

2. Apply the Fractional Exponent Rule to simplify the square root:


=\frac{256^{}(x^{(2)/(2)})^{}}{y^(-1)}=\frac{256^{}(x^1)^{}}{y^(-1)}=\frac{256^{}x^{}}{y^(-1)}

3. Finally, apply the Negative Exponent Rule:


=(256^{}x)(y^1)=256^{}xy

Therefore, the answers are:

- Expression simplified:


256^{}xy

- Rules of Exponents used to simplify it:

1. Power of a Product Rule:


(ab)^m=a^mb^m

2. Fractional Exponent Rule:


b^{(m)/(n)}=\sqrt[n]{b^m}

3. Negative Exponent Rule:


b^(-n)=(1)/(b^n)
User Jangxx
by
5.1k points